KARAKTERISTIK MORFOMETRIK RUSA SAMBAR (RUSA UNICOLOR) SEBAGAI DASAR KRITERIA SELEKSI SIFAT PERTUMBUHAN - -, Wirdateti; Brahmantiyo, Bram; Reksodiharjo, Andi; Semiadi, Gono; Dahruddin, Hadi (Jurnal Veteriner; Vol 10 No 1 (2009))
Study on the morphometric characteristic of sambar deer (Rusa unicolor) which will be used as a baseline of growth trait selection had been conducted. The aim of this study is to set up criteria for better selection of sambar deer progeny. Morphometric characteristic observed in this study including : body weight, body length, chest width, chest girth, head length, head width, ear width, and ear length respectively. Result indicated that chest girth correlates significantly with the body weight (y=-108.004+1.875x). In conclusion chest girth can be used as a criteria for selection of growth trait of sambar deer.
Keywords: morphometric, sambar deer, chest girth, growth trait